Criminal liability for illegal mining: analysis of legislative novelties - Movchan, R. O; Dudorov, O. O; Kamensky, D. V; Vozniuk, A. A; Babanina, V. V (Natsional'nyi Hirnychyi Universytet. Naukovyi Visnyk, 2022)
Purpose. Critical analysis of the criminal prohibition provided by Article 240 of the Criminal Code of Ukraine, identification of its shortcomings, development of proposals for their elimination. Methodology. The system of philosophical, general scientific and specific-scientific methods and approaches that provided for objective analysis of the subject (analysis, synthesis, induction, deduction, comparison, generalization, abstraction, sociological, statistical, formal-logical). Findings. The shortcomings of the revised Article 240 of the Criminal Code of Ukraine, in particular, the uncertainty on the issue of the minimum cost of illegally mined minerals of national importance for recognizing an act as criminally unlawful, the lack of differentiation of criminal liability for illegal mining of minerals of national importance depending on the size (value) of the extracted items, the creation of an imbalance between the degree of severity of penalties in the form of a fine, enshrined in different parts of the prohibition under consideration, the groundlessness of constructing a sanction of Part 3, Article 240 of the Criminal Code of Ukraine as non-alternative. Originality. The authors are the first in the doctrine of criminal law of Ukraine to carry out a comprehensive critical understanding of the updated version of the provision on the regulation of criminal liability for violation of the rules for the protection or use of subsoil, illegal mining, which made it possible to develop research-based recommendations for improving domestic criminal law. Practical value. Based on the results of the article, specific proposals addressed to domestic parliamentarians have been developed, which can be taken into account in the process of further lawmaking to update relevant provisions of the Criminal Code of Ukraine. It has been argued that in the improved Article 240, the minimum value of illegally mined minerals of national importance should be determined in order to recognize the act as criminally unlawful, and the same criteria for the crime of illegal mining of minerals of local and national importance should be fixed. It has been substantiated that criminal liability for illegal mining of minerals of national importance should be differentiated depending on the size (value) of the mined items. It has been proven, including through references to law enforcement materials, that in the relevant sanctions, firstly, along with imprisonment for a certain period, an alternative main type of punishment in the form of a fine should be indicated, and secondly, the imbalance between the degree of severity of punishments, provided for in different parts of the provision under consideration, should be eliminated.